فاعلية برنامج تدريبي قائم على الهناء النفسي في تخفيف حدة التجول العقلي وتحمل الضائقة لدى أمهات الأطفال متعددي الإعاقة - صالح, أحمد; الدلبحى, خالد (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الحالية إلى التعرف على فاعلية برنامج تدريبي قائم على الهناء النفسي في تخفيف حدة التجول العقلي وتحمل الضائقة لدى أمهات الأطفال متعددي الإعاقة، والكشف عن استمرارية تأثير البرنامج، وتكونت عينة الدراسة (12) من أمهات الأطفال متعددي الإعاقة تراوحت أعمارهن ما بين (25-40) عاما، بمتوسط حسابي قدره (35.67) عاما، وانحراف معياري قدره (4.91)، وقد تم تقسيمهن إلى مجموعتين تجريبية وضابطة قوام كل منهما (6) أمهات، واعتمد الباحثان على المنهج شبه التجريبي، واستخدم الباحثان مقياس التجول العقلي، ومقياس تحمل الضائقة، والبرنامج التدريبي القائم على الهناء النفسي من إعداد الباحثين، وأسفرت نتائج الدراسة عن وجود تأثير دال إحصائيا للبرنامج القائم على الهناء النفسي في تخفيف حدة التجول العقلي وتحمل الضائقة لدى أمهات الأطفال متعددي الإعاقة في المجموعة التجريبية، وفي ضوء النتائج توصي الدراسة بضرورة التدريب على الهناء النفسي مع أسر متعددي الإعاقة والاعاقات الشديدة وذلك لأنه يساعد على تخفيف كثير من الضغوط النفسية والتجول العقلي وتحمل الضائقة. Abstract: The current study aimed at identifying the effectiveness of a training program based on psychological well-being in reducing mind wandering and distress tolerance among mothers of children with multiple disabilities. It also sought to investigate the continuity of the program effect. The sample comprised (12) mother of children with multiple disabilities. They were between (25 – 40) years of age (mean age= 35.67; SD= 4.91). They were assigned into an experimental group and a control one. Each group included (6) mothers. The researchers depended on the quasi-experimental method. They administered mind wandering scale, distress tolerance scale and implemented the training program that was based on psychological well-being (They were all prepared by the researchers). Results indicated that there was a statistically significant effect of the training program based on psychological well-being on reducing severity of mind wandering and distress tolerance among mothers of children with multiple disabilities in the experimental group. According to the aforementioned results, the study recommended the necessity of training families of individuals with multiple and/or severe disabilities on psychological well-being. It may significantly help to reduce psychological stress, mind wandering and distress tolerance
مقال
Keywords: الهناء النفسي – التجول العقلي – تحمل الضائقة - متعددي الإعاقة; psychological well-being - mind wandering - distress tolerance – children with multiple disabilities